Enhanced HMGB1 Expression May Contribute to Th17 Cells Activation in Rheumatoid Arthritis. (26th October 2011) - Shi, Yan; Sandoghchian Shotorbani, Siamak; Su, Zhaoliang; Liu, Yanfang; Tong, Jia; Zheng, Dong; Chen, Jianguo; Liu, Yingzhao; Xu, Yan; Jiao, Zhijun; Wang, Shengjun; Lu, Liwei; et al.
Abstract : Rheumatoid arthritis(RA) is a common autoimmune disease associated with Th17 cells, but what about the effect of high-mobility group box chromosomal protein 1 (HMGB1) and the relationship between Th17-associated factors and HMGB1 in RA remains unknown. In the present study, we investigated the mRNA levels of HMGB1, RORγt, and IL-17 in peripheral blood mononuclear cells (PBMCs) from patients with rheumatoid arthritis by quantitative real-time PCR (RT-qPCR), and the concentrations of HMGB1, IL-17, and IL-23 in plasma were detected by ELISA. And then, the effect of HMGB1 on Th17 cells differentiation was analyzed in vitro. Our clinical studies showed that the mRNAs of HMGB1, RORγt, and IL-17 in patients were higher than that in health control (P < 0.05 ), especially in active RA patients (P < 0.05 ). The plasma HMGB1, IL-17, and IL-23 in RA patients were also higher than that in health control (P < 0.05 ); there was a positive correlation between the expression levels of HMGB1 and the amount of CRP, ERS, and RF in plasma. In vitro, the IL-17-produced CD4 + T cells were increased with 100 ng/mL rHMGB1 for 12h, which indicated that the increased HMGB1 might contribute to Th17 cells activation in RA patients.